Pengaruh Likuiditas dan Ukuran Perusahaan terhadap Return Saham pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman - Hendra Lesmana; wati erawati; Husni Mubarok; Ery Suryanti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
This study aims to test whether liquidity and company size have an influence on stock returns in manufacturing companies in the food and beverage sub-sector in 2017-2019. The total population of this study was 26 companies with a total sample of 11 manufacturing companies listed on the Indonesia Stock Exchange with a study period of three years so that the research sample was 33 data. The data used is secondary data from various reliable sources. The sampling technique used was purposive sampling method. The independent variables include liquidity and company size, while the dependent variable is stock returns. Collecting data in this study using secondary data with documentation methods. The method of analysis of this research is using multiple linear regression analysis and t test. Based on the t test shows that (1) liquidity has a significant effect on stock returns (2) company size has an influence on stock returns.The company’s ability to pay debts on time will make the stock returns be returned appropriately. Mean while, company size has a positive and insignificant effect on stock returns.